2020
DOI: 10.2147/ott.s232464
|View full text |Cite
|
Sign up to set email alerts
|

<p>Is there a CDKN2A-centric network in pancreatic ductal adenocarcinoma?</p>

Abstract: Pancreatic cancer has a high mortality rate and its incidence has risen rapidly in recent years. Meanwhile, the diagnosis and treatment of this cancer remain challenging. Pancreatic ductal adenocarcinoma (PDAC) is the most common type of pancreatic cancer, but, currently, no sufficiently effective modalities for its treatment exist. The early diagnosis rate of pancreatic cancer is low and most patients have reached an advanced stage at the time of diagnosis. PDAC evolves from precancerous lesions and is highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 152 publications
(175 reference statements)
0
20
0
Order By: Relevance
“…CDK4 can inhibit the activity of CDKN2A, which is a transcription target of MYC 31 . Moreover, other researchers showed the relationship between CDKN2A and other five genes and built up a CDKN2A‐centric network regulation which might exist in pancreatic ductal adenocarcinoma (PDCA) 32 . HNF1B mutation might affect the interaction with CDKN2A, and this might depend on the location of the mutation.…”
Section: Discussionmentioning
confidence: 99%
“…CDK4 can inhibit the activity of CDKN2A, which is a transcription target of MYC 31 . Moreover, other researchers showed the relationship between CDKN2A and other five genes and built up a CDKN2A‐centric network regulation which might exist in pancreatic ductal adenocarcinoma (PDCA) 32 . HNF1B mutation might affect the interaction with CDKN2A, and this might depend on the location of the mutation.…”
Section: Discussionmentioning
confidence: 99%
“…PDAC has four common gene mutations: KRAS, TP53, SMAD4, and CDKN2A [13,24,25]. Notably, the HER2/neu oncogene mutation typically occurs in the precancerous stage, where HER2 binds to EGFR and activates its pathway.…”
Section: Mutation Cascade Analysismentioning
confidence: 99%
“…Previous studies have reported that CDKN2A is inactivated in about 95% of PDAC by different mechanisms such as homozygous deletion of both alleles, intragenic mutation in one allele or promoter hypermethylation. CDKN2A is inactivated in about 40% of cases by deletion of both alleles [ 41 , 42 , 43 , 44 ]; another 15% of PDAC shows hypermethylation of the promoter sequence for CDKN2A [ 41 , 45 , 46 , 47 ]. Moreover, further data confirmed the role of this mutation on the PDAC progression to a more aggressive phenotype.…”
Section: Cdk4/6 Pathwaymentioning
confidence: 99%